Misused Sirens and Signal Lights Expose Enforcement Gaps in South Jakarta: Penyalahgunaan Sirene dan Lampu Isyarat Mengungkap Kesenjangan Penegakan Hukum di Jakarta Selatan - Lubis, Thondi Akbar Parlindungan; Lewoleba, Kayus Kayowuan (Academia Open, 2026)
General Background Traffic order and road safety depend on clear legal rules, public compliance, and consistent implementation by authorized institutions. Specific Background In South Jakarta, the use of sirens and signal lights by four-wheeled vehicles remains problematic because private vehicle users continue to use priority facilities that are legally reserved for specific public service and emergency vehicles under Law Number 22 of 2009. Knowledge Gap Previous studies have discussed vehicle priority facilities, legal awareness, and traffic violations, but research connecting legal regulation, field-level misuse, and officer-based implementation in a specific local jurisdiction remains limited. Aims This study aims to analyze the legal regulation of sirens and signal lights, identify misuse practices, and evaluate traffic law implementation against unauthorized use in South Jakarta. Results The findings show that private vehicle users commonly use unauthorized sirens and signal lights to gain road priority during congestion. Police responses include ticketing, warnings, and confiscation of unauthorized equipment. However, implementation remains weak due to low legal awareness, limited supervision, inadequate monitoring capacity, and road users’ tendency to prioritize convenience over regulatory compliance. Novelty This study offers an integrated normative and empirical analysis using Soerjono Soekanto’s legal effectiveness framework and field data from traffic police officers. Implications Stronger sanctions, better supervision, and continuous legal education are needed to build orderly traffic culture and reduce unauthorized priority facility use. Highlights: Private motorists used unauthorized devices to obtain priority during congestion. Sanctions included ticketing, warnings, and confiscation of equipment. Low legal awareness and limited monitoring weakened compliance. Keywords: Signal Lights, Law Enforcement, Traffic Violations, Sirens.